Preparation and characterization of glass-ceramic materials in the BaO-Li2O-ZrO2-SiO2 system and their dependence on treatment temperatures - Silveira, Cristian Berto da; Campos, Silvia Denofre de; Castro, Sandra C. de; Kawano, Yoshio (Elsevier, 1999)
The preparation and characterization of transparent glass-ceramics in the composition of 30Li2O:5ZrO2:xBaO:(100-x) SiO2 with x = 0, 5, 10, 15, and 20 mol% are described. Glasses were melted in a platinum crucible at 1100°C for 2 h and then heat-treated at 900°C for 3 h. The characterizations were performed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman and infrared spectroscopy, and scanning electron microscopy (SEM). The experimental results indicate that there was a structural change in the glass-ceramics as the BaO concentration in the mixture increased. In the XRD patterns of samples without heat treatment, only the halo was observed. After heat treatment, the appearance of the materials was verified by X-ray diffraction peaks. The reorganization of the amorphous solid was confirmed by Raman and IR spectroscopy along with XPS and SEM, with a more homogeneous phase formation being observed.
Keywords: Composition; Glass; High temperature operations; Infrared spectroscopy; Melting; Oxides; Phase transitions; Raman spectroscopy; Scanning electron microscopy; Thermal effects; X ray diffraction analysis; X ray photoelectron spectroscopy; Glass ceramic materials; Halo; Structural change; Ceramic materials